SINGLE NUCLEOTIDE POLYMORPHISMS WITHIN GENES REGULATING IMMUNE RESPONSE AND ANTIOXIDANT DEFENCE IN PATIENTS WITH COLORECTAL AND GASTRIC CANCER - Асия Дамировна Падюкова; Арсений Евгеньевич Южалин; Антон Геннадьевич Кутихин; Алексей Николаевич Волков; Юлия Александровна Попова; Алексей Станиславович Животовский; Юрий Абрамович Магарилл; Евгений Анатольевич Цитко; Елена Борисовна Брусина (Медицина в Кузбассе, 2017)
Background. During the recent decade, studies on inherited variation within innate immune response and antioxidant defense genes and cancer highlighted a number of significant associations; however, this is not the case for colorectal cancer.